How far Green Marketing Approach Could Shape Strong Green Brand. Evidences from Green Customer Indonesia - Lumban Batu, Kardison (University of Muhammadiyah Malang, 2026)
This study aims at investigating the impact GMA on Eco-Labelled Product Purchase Intention (EPPI) and Brand Relationship Output (PRO). Brand Reputation (BR) defined as the customer perception regarding on brand based on experiences, evaluation and perceived information. Good reputation is crucial for business sustainability which led to affect customer trust, loyalty and purchase decision. Quantitative method approach with causal-comparative to investigate causal relationship among GMA with brand performance output. Current research involved data collection through survey to analyze customers’ perception on GM practices by certain brands and its impact on brand reputation. Structural Equation Modeling with AMOS. 24 deployed to analysis the data. Due to complicated interactions among variables, a two-step process was conducted. The first step was to evaluate reliability and validity, followed by hypotheses analysis. Research findings showed the significant impact of GMA, SBC, CRA on EPPI & GBA.